CAUSALITY ANALYSIS OF SUCCESS IN BUILDING CREATIVE ENTERPRISES WITH ECONOMIC KNOWLEDGE: CASE STUDY OF ILLUSTRASEE SURABAYA COMMUNITY - Renowaseso Renowaseso; Irzameingindra Putri Radjamin; Joshi Maharani Wibowo (SEAN Institute, 2023)
This research aims to determine whether economic knowledge can influence success in building the profession of creative actors. This research is based on distributing questionnaires to the Illustrate creative community, SURABAYA branch. The analysis used is qualitative descriptive with a phenomenological model on the questionnaire answers. Then, the data is processed using the voyant tool instrument. From the research, the result is that artists with basic economic knowledge can sell their artwork.